Effect of passive pneumoperitoneum on oesophageal pressure, cardiovascular parameters and blood gas analysis in horses - Canola, P. A. [UNESP]; Perotta, J. H. [UNESP]; Laskoski, L. M. [UNESP]; Escobar, André [UNESP]; Melo e Silva, C. A.; Canola, J. C. [UNESP]; Johnson, P. J.; Valadao, C. A. A. [UNESP] (Wiley-Blackwell, 2011)
P>Reasons for performing study:Standing surgical procedures are being employed to an ever-greater extent in horses. Pneumoperitoneum during abdominal surgery might adversely affect the work of breathing.Objectives:To determine whether development of pneumoperitoneum during abdominal surgery adversely influences the work of breathing.Methods:Eight healthy mature horses were equipped with carotid artery and thoracic vena cava catheters and an intraluminal manometry system. The following measurements were obtained before and at +5, +10, +15 and +30 min following establishment of pneumoperitoneum by paralumbar puncture using an 8 gauge needle: vital signs, oesophageal pressure, gastric pressure, arterial and central venous blood pressures, and arterial and mixed venous blood gas analyses.Results:Significant changes in oesophageal pressure, central venous pressure and results of arterial and mixed venous blood gas analysis were not detected. Arterial diastolic and mean pressures and rectal temperature increased slightly (P < 0.05).Conclusions:Passive pneumoperitoneum did not adversely affect breathing mechanics or haemodynamic variables under experimental conditions. Changes in arterial pressure could have occurred as a response to the passive pneumoperitoneum or be related to handling stress. Subtle variations in rectal temperature were not clinically relevant and likely resulted from stress associated with restraint.Potential relevance:It is unlikely that mature horses will develop signs of respiratory difficulty as a result of the development of passive pneumoperitoneum during standing laparoscopy.
Keywords: Horse; Pleural pressure; Pneumoperitoneum; oesophagus; Blood gas analysis